What Kind of EU Fiscal Capacity? Evidence from a Randomized Survey Experiment in Five European Countries in Times of Corona - Roel Beetsma; Brian Burgoon; Francesco Nicoli; Anniek de Ruijter; Frank Vandenbroucke (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Based on a conjoint survey experiment we explore the support among European citizens for a European Union (EU) budgetary assistance instrument to combat adverse temporary or permanent economic shocks hitting Member States. Suitably designed, there is quite substantial support for such an EU instrument generally and across the sample countries. Support is broader when budgetary support is conditional on debt reduction in normal times and spent in specific policy areas, in particular healthcare and education. Support also increases when there is a role for the European Commission in terms of monitoring and providing guidance. However, there is little support for policy packages that terminate a program and impose a fine in the case of non-compliance. Further, there is broad acceptance of long-run redistribution towards poorer countries. Financing the assistance through a progressive tax increase is more popular than through a flat tax increase. In general, there is substantial scope for constructing assistance packages that command a majority support in all sample countries. The survey was fielded in the midst of the Covid-19 crisis, in which the prospect of a severe economic shock became realistic. However, the results of our survey are based on respondent views in a (partially) pre-political environment: respondents had the opportunity to reason and form their own opinion about the assistance package before concrete policy proposals were debated by political parties that seek the edges of polarization.
Keywords: E63; H23; H50; H60; 330; EU fiscal capacity; conjoint experiment; EU support instruments; temporary or permanent shocks; stabilization; conditionally; taxation; redistribution